Исправление к статье: Широв А. А., Сапова Н. Н., Узякова Е. С., Узяков Р. М. “Комплексный прогноз спроса на межрегиональные грузовые железнодорожные перевозки” // Экономика региона. 2021. Т. 17, вып. 1. С. 1-15. https://doi.org/10.17059/ekon.reg.2021-1-1 - Editorial board (Economy of Regions, 2021)
In the article “Comprehensive Forecast of Demand for Inter-regional Rail Freight Transport” by Alexander A. Shirov, Natalia N. Sapova, Elena S. Uzyakova, and Rafael M. Uzyakov, which appeared on pages 1–15 of the 1, 2021 issue, Vol. 17, the Acknowledgments section was omitted. In the online version of the paper the following text of the Acknowledgments section was added: Acknowledgments The article has been prepared with the support of a grant in the form of a subsidy for large scientific projects in priority areas of scientific and technological development in the framework of the subprogramme “Basic research for long-term development and ensuring the competitiveness of society and the state” of the state programme «Scientific and Technological Development of the Russian Federation», the project “Social and Economic Development of Asiatic Russia on The Base of The Synergy of Transport Accessibility, Systemic Knowledge about Natural Resource Potential and Expanding Space of Interregional Interactions”, the agreement No. 075-15-2020-804 with the Ministry of Science and Higher Education of the Russian Federation (internal grant No. 13.1902.21.0016). This error does not affect the conclusions of the paper. The article has been corrected online.